A STUDY OF CLINICAL AND ECHOCARDIOGRAPHIC PROFILE IN PATIENTS OF DILATED CARDIOMYOPATHY - BEHERA, BIJAYA KUMAR; NAIK, M. RADHA KRISHNA; JALI, SIBA NARAYAN; TRIPATHY, SUSMITA; BEHERA, NISARG (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Dilated cardiomyopathy (DCM) is the third most common cause of heart failure (HF) and is the most common cardiomyopathy. The present study was undertaken with the aim to study the different clinical presentations of dilated cardiomyopathy, to correlate echocardiography findings with different clinical presentations and to find out the variables which determine the poor outcomes. Methods: This prospective observational study was conducted in the Department of General Medicine of MKCG Medical College and Hospital, Berhampur, Odisha, India from November 2019 to November 2021. Fifty cases of dilated cardiomyopathy (28 males & 22 females), diagnosed on clinical and echocardiography criteria in the Department of General Medicine and Cardiology were selected for the study. Results: Out of 50 cases, there were 28(56%) males and 22(44%) females giving male to female ratio 1.27:1. Forty (80%) were idiopathic. Dyspnea was most common presenting clinical feature in 43(86%) cases. In echo study, maximum number of cases (n=21, 42%) were having ejection fraction (EF) in the range of 36-40% and maximum number of cases (n=26, 52%) had severe fractional shortening (FS). Conclusion: DCM is one of the commonest causes of heart failure and is most common type of cardiomyopathy found in middle aged and elderly male population. Biventricular failure followed by left ventricular failure was the most frequent clinical presentation. Early identification and treatment are very essential to improve cardiac function and alleviate patient symptomology.